PENGARUH LITERASI KEUANGAN, PERENCANAAN KEUANGAN DAN KONTROL DIRI TERHADAP PENGELOLAAN KEUANGAN UMKM DI KOTA MEDAN - Feroza, Elza; Parhusip, Austin Alexander (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
This research aims to analyze the influence of financial literacy, financial planning, and self-control on the management of Micro, Small, and Medium Enterprises (UMKM) in Medan City. MSMEs have a strategic role in the national economy, but still face obstacles in the form of low financial literacy, limited access to financial services, and the implementation of management strategies that are not optimal. This research uses a quantitative approach with a survey method. The research sample consists of 100 UMKM actors in the culinary sector in Medan City which was selected through the purposive sampling technique. Data collection was carried out using a questionnaire with the Likert scale and analyzed through multiple linear regression, t-test, F-test, and determination coefficient. The research results show that financial literacy, financial planning, and self-control have a positive and significant effect on the financial management of MSMEs both partially and simultaneously. This finding indicates that the increase in understanding of financial literacy, the expansion of access to formal financial planning, and the implementation of proper financial management can strengthen the weaknesses of the competitiveness system and the sustainability of MSMEs in Medan City. This research is expected to be a reference for MSMEs, governments, and financial institutions in formulating more effective MSME financial management strategies. Keywords: Financial Literacy; Financial Planning; Self Control; MSME Financial Management; Medan